Comparison of Test Your Memory and Montreal Cognitive Assessment Measures in Parkinson’s Disease - Emily J. Henderson; Howard Chu; Daisy M. Gaunt; Alan L. Whone; Yoav Ben-Shlomo; Veronica Lyell (Parkinson's Disease)
Background. MoCA is widely used in Parkinson’s disease (PD) to assess cognition. The Test Your Memory (TYM) test is a cognitive screening tool that is self-administered. Objectives. We sought to determine (a) the optimal value of TYM to discriminate between PD patients with and without cognitive deficits on MoCA testing, (b) equivalent MoCA and TYM scores, and (c) interrater reliability in TYM testing. Methods. We assessed the discriminant ability of TYM and the equivalence between TYM and MoCA scores and measured the interrater reliability between three raters. Results. Of the 135 subjects that completed both tests, 55% had cognitive impairment according to MoCA. A MoCA score of 25 was equivalent to a TYM score of 43-44. The area under the receiver operator characteristic (ROC) curve for TYM to differentiate between PD-normal and PD-cognitive impairment was 0.82 (95% CI 0.75 to 0.89). The optimal cutoff to distinguish PD-cognitive impairment from PD-normal was ≤45 (sensitivity 90.5%, specificity 59%) thereby correctly classifying 76.3% of patients with PD-cognitive impairment. Interrater agreement was high (0.97) and TYM was completed in under 7 minutes (interquartile range 5.33 to 8.52 minutes). Conclusions. The TYM test is a useful and less resource intensive screening test for cognitive deficits in PD.